Alginate versus addition silicone: What is the best material for removable partial dentures? (Research, Society and Development, 2024)
Objective: The objective of this study was to create a narrative literature review article, covering two different types of materials: silicone and alginate, with the aim of seeing which is the best material to compose a removable partial denture. Methodology: The searches were carried out in PUBMED Central, Web of Science, VHL/BIREME, Brazilian CAPES, Scielo and using the Google Academy portal. A total of 24 articles were acquired that address the benefits and harms of using silicone and alginate in removable partial dentures, in addition to their differences. We consult periodicals and books, aiming to obtain more reliable information on the topic. In order to carry out a literature review, the vision of Mattos (2015) was used to structure the article. Results: During the study, it was seen that addition silicone is widely considered the best material due to its high precision, excellent ability to reproduce details and superior dimensional stability, however alginate is more economical and easier to use, it is more suitable for preliminary impressions and situations where extreme precision is not essential.